O curso de Licenciatura em Educação do Campo: Pedagogia da Terra e a especificidade da formação dos educadores e educadoras do campo de Minas Gerais - Sonia Maria Roseno (2010)
This work aimed to analyze a set of actions and experiences from the Bachelor Course in Rural/Country Education: Pedagogy of the Land at the Education Faculty of UFMG1. We sought the understanding of its internal organicity, and in order to do so, we cast an attentive look at this innovative practice which arose within the articulation of a structure of thelearners representation amidst the realm of the course. We analyzed, mainly, how the specificities and protagonism in the learners background arose in the proceedings of its internal organicity. The organizational dynamics mediated the distinction and the intertwiningof being an activist and being a learner. Taking into account that these learners are members of Social Movements, considered by many authors the locus of constructed learning in the context of social conflicts (ARROYO, 2003; CALDART, 2000), and yet we can notice thatthe inclusion of these characters in the Movements provide identity traces which distinguishes them as a collective character (CASTELLS; 1999; HALL, 1997; CALDART, 2002). The education stemming from the Movements added to the guiding principles of the CoursesPolitical Pedagogical Project and its directions. In this sense, it got embodied under the Rural/Country Education concepts (KOLLÍNG; 1999), thus, it was conceived to comprise both theory and practice so that theyd meet in all learning processes (FREIRE, 1970). We interviewed 06 learner-characters, 02 coordinator-characters and 02 teacher-characters. The material brought about by the interviews was analyzed under Marxs historical dialectical materialism theoretical framework. The embodying of the internal organicity revealed that the characters of the Movements have their own way to inter-relate themselves with the new realities ahead of them. We then noticed that the introduction of the Course with a specific and differentiated attribute has opened new perspectives to UFMG community, Social Movements and partners, what outlines the possibility of new forms of knowledge and learning in a process mediated by dialogue and for an education focusing the reality of thepeople involved in it.